THE EFFECT OF BEAM ECCENTRICITY ON THE LOAD CARRYING CAPACITY OF REINFORCED CONCRETE WIDE BEAM-COLUMN JOINT - Suliman Ghazi Omar (My University, 2022)
Abstract Background: The beam-column joints of reinforced concrete (RC) are one of the elements in RC structures that have significant influence on the load transfer path. Buildings use two types of RC joints based on beam width: conventional joints and wide beam-column joints. Objective: The advantages of the wide and shallow RC beam-column joints in frame system are more economical, easier to build, provide a flexible space and less obstruction. This system is most used in Middle Eastern countries and hence is selected to be the subject of this study. The system consists of a one-way monolithic ribbed slab that is supported by concealed and wide beams. In some cases, the wide beam-column joint has eccentricity due to architectural considerations, where the center of the wide beam does not coincide with the center of the column. Methodology: The structural behaviour of eccentric wide beam-column joint is not fully understood due to the limited experimental research compared to those of conventional frame structures. This research concentrates on the effect of eccentricity on the load carrying capacity of RC edge wide beam-column joint within moment resisting frame (MRF). Finite Element (FE) analysis using (ABAQUS) is conducted to investigate the moment capacity of RC wide beam-column joint. The model is validated based on available experimental results. Results: and the results are further used to compare the change in bending moment capacity of the beam with and without eccentricity where the present of eccentricity produce additional torsion on wide beam and therefore reduce the bending moment capacity. Conclusion: An analytical approach is developed to predict the torsional moment on wide beam and use it to find the bending moment capacity. The proposed approach is derived based on principles of mechanics and equilibrium. The results from the approach are found to be consistent with the FE results. Keywords: eccentricity, wide beam, edge beam, wide beam column joint, eccentric wide beam-column joint, bending capacity, torsional moment on edge beam.